O governo Chávez e a luta pelo poder na Venezuela: uma análise dos atores políticos em conflito - Fukushima, Kátia Alves (2009)
The main objective of this study is to analyze the factors that explain the reactions of the opposition sectors to the government of Hugo Chávez between 2001 and 2004. The understanding of these reactions is searched having as background the break with the liberal democratic regime occurred in 1999, with the up rise of this president, inaugurating what it calls democracia participativa y protagónica . To achieve its objectives this work try to understand initially the political regime in the country since the construction of liberal democracy around the Pact of Punto Fijo, through its crisis during the 1980s, until the election of Chavez in 1998. Finally, we present some interpretations on the political and institutional changes occurred with the new government and what they may represent in the sectors linked to the former regime that arise in opposition. The findings indicate that the reactions of these sectors to the government initiated in 1999, resulted from its displacement from the power, and not as they stated in their dissatisfaction with the "authoritarianism" of the new regime. What they pursued was the control of the state, allowed by the minimalist nature of democracy pre-Chávez.